Corruption as a Social Problem and its Implication on Nigerian Society: A Review of Anticorrupt Policies - Bassey, Antigha Okon; Abia, Raphael Pius; Frank, Attah; Bassey, Umo Antigha (Richtmann Publishing, 2013)
This paper examines corruption as one of the major social problems in Nigerian society. Though corruption in society isdiscussed generally, emphasis is placed on official corruption. The analysis was based on secondary data obtained from text,newspapers and archival materials. The scope of the paper covers; conceptual analysis, review of anti-corruption policies; acritique of corruption control efforts in Nigeria; prospect of eradicating corruption in Nigeria, recommendations and conclusion.This paper presents a critical analysis of government policies on corruption control, the effects of which are not felt by ordinaryNigerians, suffering from the consequences of corruption and the problems such policies faced. The paper provided possiblerecommendations for the elimination of corruption which include among others: professionalization of public service and theremoval of bureaucratic conditions which promotes corruption.